2017
DOI: 10.1002/ecy.1975
|View full text |Cite
|
Sign up to set email alerts
|

Warming effects on permafrost ecosystem carbon fluxes associated with plant nutrients

Abstract: Large uncertainties exist in carbon (C)-climate feedback in permafrost regions, partly due to an insufficient understanding of warming effects on nutrient availabilities and their subsequent impacts on vegetation C sequestration. Although a warming climate may promote a substantial release of soil C to the atmosphere, a warming-induced increase in soil nutrient availability may enhance plant productivity, thus offsetting C loss from microbial respiration. Here, we present evidence that the positive temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 43 publications
4
40
0
Order By: Relevance
“…, Sardans and Peñuelas , Li et al. ). Plant nutrient concentrations are positively correlated with leaf area‐based photosynthetic rates in arid and semiarid grassland plants (Wright and Westoby , Liu et al.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…, Sardans and Peñuelas , Li et al. ). Plant nutrient concentrations are positively correlated with leaf area‐based photosynthetic rates in arid and semiarid grassland plants (Wright and Westoby , Liu et al.…”
Section: Discussionmentioning
confidence: 98%
“…Because nitrogen (N) and phosphorus (P) are essential nutrients for plant growth, maintenance, and reproduction (Reich and Oleksyn , Li et al. , Sardans et al. ), understanding the effects of increasing drought on the biogeochemistry of N and P is needed (Sardans and Peñuelas ).…”
Section: Introductionmentioning
confidence: 99%
“…Although warming‐induced changes in GPP were closely correlated with LAI dynamics, it partly explained the variance of GPP, indicating that other factors may co‐regulate the response of GPP to experimental warming. Previous studies showed that soil temperature, soil moisture, and leaf N concentration were important factors in regulating GPP (Li et al, ; Luo, ; Peng, Li, et al, ), because these factors can affect the chlorophyll content and enzyme activity, which are associated with plant photosynthesis (Chapin et al, ; Shaver et al, ). Nevertheless, we did not observe significant relationships of GPP with soil temperature, soil moisture, and leaf N concentration (Figure S8 and Table S5), suggesting that these factors are not responsible for the remaining variance of GPP in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The soil active layer (the layer of seasonally thawed soil above the permafrost) is ~4.0 m deep. Mean annual temperature is −3.4°C and mean annual precipitation is 466 mm (Li et al, ). The soil is classified as Cambisols based on the soil classification system of FAO (Lu et al, ), with 2.1% clay, 54.2% silt and 43.7% sand.…”
Section: Methodsmentioning
confidence: 99%
“…We tested these hypotheses with a 4‐year deployment of open‐top chambers (OTCs) in a marsh meadow on the Tibetan Plateau. We selected a marsh meadow ecosystem because it has high SOC density (65 kg C/m 2 ; Ding et al, ) and strong decomposability relative to other ecosystems on the Tibetan Plateau (Chen et al, ), and also because it has high soil moisture so that experimental warming does not alter soil hydrology (Li et al, ), allowing the isolation of temperature effects. We first examined the warming effects on plant biomass, growing‐season soil CO 2 efflux and SOC stocks from 2014 to 2016, and then quantified changes in SOM molecular composition in the top 30 cm in the fourth experimental year using 13 C‐NMR and biomarker analyses.…”
Section: Introductionmentioning
confidence: 99%